Utilization of fruit wastes for enzyme production in submerged fermentation (International Journal of Biology and Chemistry, 2020)
This study was aimed to produce enzymes by co-culturing of Bacillus megaterium and Saccharomyces cerevisiae using fruit waste as sole substrate in submerge fermentation. Maximum amylase production (1.208 ± 0.14IU/ml) was observed in fresh melon peel substrate after 48 h. Maximum filter paper activity (0.645 ± 0.02IU/ml) and tannase (0.25 ± 0.01IU/ml) production was noted after 24 h from rotten peach. Sweet lemon peels yielded highest carboxymethyl cellulase (0.435± 0.02 IU/ml) production after 24h of fermentation. Maximum reducing sugars (2.537± 0.07 mg/ml) and total sugars (17.703 ± 0.13 mg/ml) liberation was observed from sweet lemon peels after 24h. Maximum ethanol production (0.56 ± 0.03 mg/ml) was also found from sweet lemon peel after 72h of fermentation. Findings of this study showed that fruit waste had potential for production of bioactive compounds via microbial fermentation